A history of technology and invention : (John Murray, 1980)
This book introduce about methods of producing power, the machine industries, transportation and communication, military techniques, constructing and equipping urban buildings, the extraction and exploitation of natural resources, the textile industries, techniques of expression, the spread of technical progress.